A literatura crossover de fantasia e as temáticas fraturantes em Harry Potter e o prisioneiro de Askaban e Porém bruxa - Seixas, Maria Victória Ruela de (2023)
This work aims to address the history of youth literature, the crossover phenomenon and the literary fantasy, in addition to analyzing how fractured themes present themselves in works that fit into these respective categories. The importance of this study is justified by observing the precariousness of studies on fantasy books in Brazil, a segment that continues to grow over time around the world, especially when aimed at young audiences. From the question of how fractured themes could be approached by authors through a surreal narrative, the hypothesis was pointed out that fantasy literature is the ideal genre to debate these issues in such a way that young readers in training understand in a way more playful. The main objectives are: to understand how youth literature was established and improved over the centuries; explore the development of the crossover phenomenon as a literary driver, especially in the fantasy genre; help enrich the critical fortune of fantasy literature studies in Brazil. The bibliographic and qualitative dissertation is organized into three chapters, starting with a historical overview of youth literature and young people's consumption behavior based mainly on studies by researchers Diana Navas, Ana Margarida Ramos and Teresa Colomer; in addition to addressing the proposal of quality literature for all audiences, the crossover literature studied by Sandra Beckett and Rachel Falconer. Sequentially, the aim is to list the great literary phenomena of fantasy and explain how this genre is structured and essentially characterized based on the research of Farah Mendlesohn, , Tzvetan Todorov and others. To conclude, there will be a brief explanation of what the idea of fracturing themes consists of, and an analysis of these themes present in the fantastic works Harry Potter and the Prisoner of Askaban by J. K. Rowling and Porém Bruxa by Carol Chiovatto